2015
DOI: 10.1021/acsnano.5b00436
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Boron-Doped Laser-Induced Graphene Microsupercapacitors

Abstract: Heteroatom-doped graphene materials have been intensely studied as active electrodes in energy storage devices. Here, we demonstrate that boron-doped porous graphene can be prepared in ambient air using a facile laser induction process from boric acid containing polyimide sheets. At the same time, active electrodes can be patterned for flexible microsupercapacitors. As a result of boron doping, the highest areal capacitance of as-prepared devices reaches 16.5 mF/cm(2), 3 times higher than nondoped devices, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
404
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 607 publications
(424 citation statements)
references
References 55 publications
15
404
2
3
Order By: Relevance
“…The capacitance slightly decreases (96% of retention) as the number of cycles increases up to 10 000, confi rming the good electrochemical stability of the proposed devices, with stability performance comparable to recently published boron-doped LIG supercapacitors. [ 28 ] The LIG/PDMS supercapacitors show also excellent mechani cal performance without signifi cant sacrifi ce of their electrochemical storage properties. During the stretching and bending process, from 0% to 50% and from 0° to 160° respectively, the CVs of the LIG/PDMS device retain quasi-rectangular shapes and remain almost unchanged even at the high scan rate of 10 V s −1 indicating the remarkable stability under deformation of the here proposed energy storage devices ( Figure 4 ).…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…The capacitance slightly decreases (96% of retention) as the number of cycles increases up to 10 000, confi rming the good electrochemical stability of the proposed devices, with stability performance comparable to recently published boron-doped LIG supercapacitors. [ 28 ] The LIG/PDMS supercapacitors show also excellent mechani cal performance without signifi cant sacrifi ce of their electrochemical storage properties. During the stretching and bending process, from 0% to 50% and from 0° to 160° respectively, the CVs of the LIG/PDMS device retain quasi-rectangular shapes and remain almost unchanged even at the high scan rate of 10 V s −1 indicating the remarkable stability under deformation of the here proposed energy storage devices ( Figure 4 ).…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…Laser induced carbonization from polymer lms was rst demonstrated for the fabrication of high-performance carbon MSCs by using high-power CO 2 infrared pulse lasers and 522 nm pulse lasers. [45][46][47][48][49] Recently, we demonstrated the fabrication of highperformance all-solid-state exible carbon MSCs by laser direct writing on polyimide (PI) lms in air using a relatively low-power compact continuous-wave blue-violet semiconductor laser with a wavelength of 405 nm, the power of which can almost be totally absorbed by the PI lm. 50 We further conducted the similar laser direct writing process on PI lm with only changing the air to inert atmosphere with argon (Ar) gas, resulting in highly increased conductivity, specic surface area, and pore size distribution, thus greatly improved energy and power densities.…”
Section: -31mentioning
confidence: 99%
“…Further analysis of the irradiated areas using transmission electron microscopy revealed that the laser process liberated carbon monolayers from the PI substrate, creating a porous graphene network on the sample surface. This discovery led to the now widespread use of laser-induced graphene for developing DLW capacitors [20][21][22] and sensors [23].…”
Section: Introductionmentioning
confidence: 99%